Codependency in the Relations of Couples of Imprisoned Women - Luz Adriana Aristizábal (Social Sciences, 2020)
Female criminal behavior has sparked the interest of many researchers who, from different perspectives, have tried to identify what are the factors that lead them to commit a crime. Studies indicate that female affective bonds change into a potentiator of crime behavior and/or withdrawal of it. The objective of this study was to find out if the couple’s bonds (previous or during the prison) were codependent, and to analyze the possible relation between the latter and female crime. This qualitative study used mixed tools in a sample of 27 women in the Bucaramanga prison (Colombia). The I-CO instrument was applied analyzing the four codependency factors: (1) denial mechanisms; (2) incomplete identity development; (3) emotional repression and (4) rescue orientation. The qualitative data obtained through the in-depth interview and focus groups were also analyzed, showing mainly three emerging categories: (1) I did it for him; (2) Although he doesn’t love me; and (3) I preferred to remain silent. The results suggested the difficulty of leaving violent relationships and the possible interaction between codependency, violent partner relationships and female crime. This research raises the need to strengthen the empowerment of women inside and outside the prison.